2015
DOI: 10.21608/jppp.2015.74934
|View full text |Cite
|
Sign up to set email alerts
|

EFFICIENCY OF SILICA NANOPARTICLES, TWO BIOINSECTICIDES, PEPPERMINT EXTRACT AND INSECTICIDE IN CONTROLLING COTTON LEAFWORM, Spodoptera littoralis BOISD. AND THEIR EFFECTS ON SOME ASSOCIATED NATURAL ENEMIES IN SUGAR BEET FIELDS

Abstract: This experiment was carried out at El-Riad region, Kafr El-Sheikh Governorate during two sugar beet successive seasons, 2013 and 2014. The aim of this study examined the efficiency of silica nanoparticles, bioinsecticides (Dipel 2X and Biofly), peppermint extract and insecticide (Match 50% EC) in controlling the cotton leafworm, Spodoptera littoralis (Boisd.) and their effects on some associated natural enemies in sugar beet. Results showed that the chemical insecticide (marshal) was the highest efficiency in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…This is in contrast to the field test of silica NPs on sugar beet infested by S. littoralis , the same pest as in this study, which does not increase the populations of predators such as Chrysoperla and Coccinella spp. 14 , suggesting that the attractive effect of silica NPs on predators depends on plant species. Our field experiments showed a short-term increase in predators on the soybean infested by a chewing insect but not on the faba bean infested by insects with other feeding types.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in contrast to the field test of silica NPs on sugar beet infested by S. littoralis , the same pest as in this study, which does not increase the populations of predators such as Chrysoperla and Coccinella spp. 14 , suggesting that the attractive effect of silica NPs on predators depends on plant species. Our field experiments showed a short-term increase in predators on the soybean infested by a chewing insect but not on the faba bean infested by insects with other feeding types.…”
Section: Discussionmentioning
confidence: 99%
“…Mousa et al 13 ; Supplementary Table S1 ). The in-field effects of silica NPs have been evaluated for a limited number of insect pests and they are negative and dose-dependent; evaluated species include a chewing insect [moth: Spodoptera littoralis 14 ], a piercing-sucking insect [aphid: Aphis craccivora 15 ], and an internal feeder [leafmining fly: Liriomyza trifolii 15 ] (Supplementary Table S1 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have revealed the importance of silica application on increasing plant growth significantly [9] . Silicon has generally not been considered essential for plant growth, although it is well recognized that many plants, particularly family Poaceae, have high silica content [10,11] concluded that spray of silica nanoparticles has reduced the cotton infestation by cotton bollworm, Pectinophora gossypiella. The application of silicon in coproduction provides a viable component of integrated management of pests because it leaves no pesticide residues in food and environment, and can be easily integrated with other pest management practices, including biological control [12] .…”
Section: Introductionmentioning
confidence: 99%
“…The available literature on the entomotoxic effects of SiO2NPs focuses on insect pests of stored grains, such as Sitophilus oryzae (Goswami et al 2010;Debnath et al 2011), Callosobruchus maculatus (Rouhani et al 2012;Arumugam et al 2016), and Corcyra cephalonica (Vani and Brindhaa 2013). More recently, entomotoxic effects have also been tested on insect pests in field settings, including the lepidopterans Spodoptera littoralis (El-Samahy et al 2015;Ayoub et al 2017), Spodoptera litura, Achaea janata (Rani et al 2014), Mythimna separata (Mousa et al 2014) and Plutella xylostella (Shoaib et al 2018;Bilal et al 2020), as well as the aphids Lipaphis pseudobrassicae (Debnath et al 2010), Aphis gossypii (Pavitra et al 2018, and the mealybug Phenacoccus solenopsis (Pavitra et al 2018). These insects are external feeders and internal leaf feeders such as leafminers have not been well studied of SiO2NP effects.…”
Section: Introductionmentioning
confidence: 99%